Effectiveness of Various Botanical Insecticides for Controlling Liriomyza sp. Pests - Akram, Ahdiatsa Hairi; Sudarmawan, A.A. K; Sudantha, I Made (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The use of botanical insecticides presents a promising alternative for controlling Liriomyza sp. pests, which often damage horticultural crops. This study examines the effectiveness of various botanical insecticide materials, such as extracts from neem leaves, tobacco, and other plants containing bioactive compounds like alkaloids and terpenoids. Literature reviews indicate that botanical insecticides work through mechanisms such as feeding inhibition, growth disruption, and increased pest mortality, demonstrating effectiveness comparable to synthetic insecticides. Factors such as concentration, application methods, and environmental conditions influence the efficacy of botanical insecticides. In addition to being environmentally friendly, botanical insecticides offer advantages such as rapid biodegradability and safety for non-target organisms. However, challenges such as low compound stability and the need for more frequent applications remain significant limitations. This study highlights the importance of farmer training to enhance the adoption of this eco-friendly technology in sustainable agricultural practices.